Retinal capillary microvessel morphology changes are associated with vascular damage and dysfunction in cerebral small vessel disease. Issue 2 (February 2023) - Wiseman, Stewart J; Zhang, Jun-Fang; Gray, Calum; Hamid, Charlene; Valdés Hernández, Maria del C; Ballerini, Lucia; Thrippleton, Michael J; Manning, Cameron; Stringer, Michael; Sleight, Emilie; Muñoz Maniega, Susana; Morgan, Alasdair; et al.
Cerebral small vessel disease (SVD) is a cause of stroke and dementia. Retinal capillary microvessels revealed by optical coherence tomography angiography (OCTA) are developmentally related to brain microvessels. We quantified retinal vessel density (VD) and branching complexity, investigating relationships with SVD lesions, white matter integrity on diffusion tensor imaging (DTI) and cerebrovascular reactivity (CVR) to CO2 in patients with minor stroke. We enrolled 123 patients (mean age 68.1 ± SD 9.9 years), 115 contributed retinal data. Right (R) and left (L) eyes are reported. After adjusting for age, eye disease, diabetes, blood pressure and image quality, lower VD remained associated with higher mean diffusivity (MD) (standardized β; R −0.16 [95%CI −0.32 to −0.01]) and lower CVR (L 0.17 [0.03 to 0.31] and R 0.19 [0.02 to 0.36]) in normal appearing white matter (NAWM). Sparser branching remained associated with sub-visible white matter damage shown by higher MD (R −0.24 [−0.08 to −0.40]), lower fractional anisotropy (FA) (L 0.17 [0.01 to 0.33]), and lower CVR (R 0.20 [0.02 to 0.38]) in NAWM. OCTA-derived metrics provide evidence of microvessel abnormalities that may underpin SVD lesions in the brain.